2017
DOI: 10.1111/aor.12929
|View full text |Cite
|
Sign up to set email alerts
|

Control of a Pediatric Pulsatile Ventricular Assist Device: A Hybrid Cardiovascular Model Study

Abstract: The aim of this work is to study pediatric pneumatic ventricle (PVAD) performance, versus VAD rate (VADR) and native heart rate (HR) ratio Rr (VADR/HR). The study uses a hybrid model of the cardiovascular system (HCS). HCS consists of a computational part (a lumped parameter model including left and right ventricles, systemic and pulmonary arterial and venous circulation) interfaced to a physical part. This permits the connection of a VAD (15 mL PVAD). Echocardiographic and hemodynamic data of a pediatric pati… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
7
2

Relationship

2
7

Authors

Journals

citations
Cited by 14 publications
(9 citation statements)
references
References 18 publications
0
9
0
Order By: Relevance
“…Ferrari and colleagues reported that in the case of asynchronous assistance, frequency beats are always present and the beat rate is equal to the difference between heart rate and the VAD rate. Moreover, they concluded that the VAD rate should be set with the aim of minimizing the frequency beat effects to reduce the right ventricular loading and to increase the left ventricular unloading .…”
Section: Discussionmentioning
confidence: 99%
“…Ferrari and colleagues reported that in the case of asynchronous assistance, frequency beats are always present and the beat rate is equal to the difference between heart rate and the VAD rate. Moreover, they concluded that the VAD rate should be set with the aim of minimizing the frequency beat effects to reduce the right ventricular loading and to increase the left ventricular unloading .…”
Section: Discussionmentioning
confidence: 99%
“…These two operation modes correspond to mild and congestive heart failure states, respectively. An acute heart failure state in pediatric patient with the body mass of 15.2 kg [25] was simulated on PMC to investigate the energetic characteristics of the Sputnik PRBP.…”
Section: Methodsmentioning
confidence: 99%
“…The hybrid model of the human cardiovascular system was previously described in The model consists of two main parts , (Fig. ): (i) A numerical part composed by a lumped parameter model, where the heart is represented by variable elastance model, heart valves are represented with a diode resistance series and the circulatory sections are represented by windkessel models.…”
Section: Methodsmentioning
confidence: 99%
“…The hybrid model of the human cardiovascular system was previously described in (5)(6)(7)(8) The model consists of two main parts (5-8), ( Fig. 1):…”
Section: The Hybrid Modelmentioning
confidence: 99%